Efforts To Improve Health And Physical Fitness Through Sports At Fitness Centers - Nur Ainul Fitri; Bamo Nabaz Mahmud; Thearonn Hang (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to determine the efforts desired by members in an effort to improve health & fitness and the results obtained by members after following the training program. Methodology: The method used in this study is a description with a qualitative approach. Data collection techniques used are based on online interview guides, observations, libraries and documentation. The subjects in this study were all fitness center members. in the period January-March who were willing to fill out the interview guide and a total of 46 people were obtained. Main Findings: The results of the study showed that members of Fitness Health and Sport Center exercise to improve health by 65% ​​and improve fitness by 35% from the exercise program, namely the weight loss program (fat lose), body shaping program (body shaping), physical fitness, weight gain, muscle mass (body building), weight training program and strength program. It is concluded that the efforts of these results can be known based on factors that influence the success of the program and the benefits obtained after running the exercise program. Novelty/Originality of this study: This study offers novelty by evaluating the effectiveness of fitness center-based exercise as an alternative strategy to improve physical health and fitness, particularly among urban populations with limited time and space for conventional physical activity.